New Research on Sexual Orientation and Gender Identity Discrimination: Effect of State Policy on Charges Filed at the EEOC. Issue 8 (2nd July 2020) - Baumle, Amanda K.; Badgett, M. V. Lee; Boutcher, Steven
ABSTRACT: In 2013, the Equal Employment Opportunity Commission (EEOC) began allowing anyone who believed that they experienced sexual orientation or gender identity (SOGI) discrimination to file charges of sex discrimination under Title VII of the Civil Rights Act. Very little is known about the impact of the EEOC's decision and whether it has enhanced protections for LGBT people. In this brief report, we present preliminary findings on trends and patterns in charge filing, paying particular attention to differences that emerge in charges filed in states with and without SOGI employment nondiscrimination laws. Differences in the characteristics of charging parties, allegations, and charge outcomes suggest that legal protections operating at the state level shape the experiences and disputing behaviors of LGBT individuals in pursuing Title VII remedies.